TECHNOLOGIES FOR RESOLVING NETWORK CONFLICTS - Bankouskaya , Yulia (The Journal of V. N. Karazin Kharkiv National University, Series Philosophy. Philosophical Peripeteias, 2021)
The study and understanding of modern technological processes, occurring in society, ambivalent nature leads to the need to clarify network processes. Social networks gradually become not only a theoretical construct, but also an empirical object included in the sphere of human daily life. Uncontrollability, anonymity, lack of unified value orientations and a strict system of control over the transmission of information, multi-channel, hypertextuality, and interactivity inherent in network interaction make it difficult to resolve conflicts. In order to reduce the level of acute contradictions, the main measures regulating people’s activities within the information and communication space should be taken. The study of social capital as a basic phenomenon that determines the specifics of the network structures interaction is caused by the fact that this capital is a resource that has a direct impact on the quality of the network, its functioning and development. The mechanisms of its distribution are used to build attitudes, activities, and a model of people’s behavior in network foundation. It acts as an information resource that affects the causes of conflict, the specifics of its unfolding, and the development of measures to resolve contradictions. The study of social capital allows us to clarify the features of network conflicts that consist in their anonymity, openness, sensory distancing, lack of sanctions and legal consequences for violation of social norms. Symbolic information space in this case acts as the main sphere of unfolding the confrontation. The importance of network conflict resolution establishes controlling over the conflict situation and developing measures to resolve it, searching for means and ways to achieve the desired result, and elaboration options for preventing the negative productivity of the problem, preventing the escalation of violence and destruction of the existing forms of social system functioning. It contributes to its transformation into more humane relationships of people to each other, interests and changes in life aspirations.